Sex-specific differences in ICOS+ T helper cell differentiation in systemic lupus erythematosus patients with low disease activity - Wu, Lisa; Kälble, Florian; Lorenz, Hanns-Martin; Zeier, Martin; Schaier, Matthias; Steinborn-Kröhl, Andrea (Clinical and experimental medicine, 2024)
Systemic lupus erythematosus (SLE) is a sex biased chronic autoimmune disease affecting predominantly females during reproductive ages. Changes in the ratio of inducible costimulatory molecule (ICOS)+ regulatory (Treg) and non-regulatory responder (Tresp) CD4+ T cells proved to be crucial for the occurrence of high disease activity. Here, we investigated how the differentiation of ICOS+CD45RA+CD31+ recent thymic emigrant (RTE) Tresps into CD45RA−CD31− memory Tresps affects the percentages of ICOS+ Tresps within total CD4+ T cells. Three different pathways (pathway 1 via CD45RA−CD31+ memory Tresps, pathway 2 via direct proliferation and pathway 3 via resting mature naïve CD45RA+CD31− (MN) cells) were examined in healthy controls and SLE remission patients separated by sex. In female SLE remission patients, immunosuppressive therapy inhibited the ICOS+ RTE differentiation via CD45RA−CD31+ memory Tresps and direct proliferation, leaving an age-independently increased differentiation into CD45RA−CD31− memory Tresps by conversion of resting MN Tresps compared with healthy controls. Due to exhaustion of this pathway with age, no age-dependent change in the percentages of ICOS+ Tresps within total CD4+ T cells could be found. In contrast, no age-independently increased differentiation could be detected in men due to sufficient immunosuppression of all three pathways. This allowed an age-dependent differentiation of ICOS+ RTE Tresps into CD45RA−CD31− memory Tresps by conversion of resting MN Tresps, resulting in age-dependently increasing percentages of ICOS+ Tresps within total CD4+ T cells. We hypothesize that the sex-specific differential effect of immunosuppression on the differentiation of ICOS+ Tresps may explain the sex- and age-dependent occurrence of high disease activity.
Online veröffentlicht: 01. März 2024
Gesehen am 11.07.2024
Im Titel ist das Pluszeichen hochgestellt